Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5530/pj.2020.12.3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Cytotoxicity of Hibiscus sabdariffa Linn Extracts on A549 Lung Cancer Cell Line

Abstract: Background: Lung cancer is the one of the leading causes of cancer death. However, current treatments for lung cancer are expensive and show negative side effects. Therefore, the study concerning natural anticancer from plants has intensified. Hibiscus sabdariffa Linn are Indonesian herb plants which have been consumed as a drink, are known to have anticancer activity against several cancer cell lines. However, its potential cytotoxic activity on A549 lung cancer cell line is still unclear. Objective: This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…The anticancer potential of Hibiscus sabdariffa leaves extracts (methanol, ethanol, ethyl acetate and chloroform) on hepatocellular carcinoma cell line Hep 3B was tested and methanolic extract showed a greater cytotoxic effect when compared with others [70]. Ethanol, ethyl acetate and hexane extracts of Hibiscus sabdariffa Linn are found to be potential natural anticancer agents against A 549 lung cancer cell line [71]. In another study the effects of Hibiscus sabdariffa aqueous extract had been evaluated against cyclophosmsmide (CPA) on male Wistar rats treated with monosodium glutamate.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…The anticancer potential of Hibiscus sabdariffa leaves extracts (methanol, ethanol, ethyl acetate and chloroform) on hepatocellular carcinoma cell line Hep 3B was tested and methanolic extract showed a greater cytotoxic effect when compared with others [70]. Ethanol, ethyl acetate and hexane extracts of Hibiscus sabdariffa Linn are found to be potential natural anticancer agents against A 549 lung cancer cell line [71]. In another study the effects of Hibiscus sabdariffa aqueous extract had been evaluated against cyclophosmsmide (CPA) on male Wistar rats treated with monosodium glutamate.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Nevertheless, the phenolic and flavonoid-rich crude ethanol extracts of PF-L exhibited the lowest required concentration to become 50% cytotoxic to DU-145 cells. It indicates that PF-L has deficient activity relative to potent anticancer plant extracts [ 45 , 46 , 47 ]. This activity could signify that metabolites at low concentrations are more bioactive or that major metabolites require high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that damaged cellular machinery of autophagy is linked with genomic instability, tumorigenesis, and malignant transformation In addition, animal models lacking Beclin 1 developed spontaneous tumors more than their control counterparts. Autophagy-related gene 5 and 7 (ATG5 and ATG7) plays a crucial role in tumor suppression, as their reduced expression caused mitochondrial damage and oxidative stress (OS) culminating in hepatic tumor development in mice [ 81 ]. Dysregulation of the PI3K/AKT pathway and impairment of its key protein associate like phosphatase and tensin homolog reduces autophagy in malignant cells and backs tumorigenesis conversely; the AKT/mTOR signaling is known to suppress autophagy.…”
Section: Effect Of Hs Phytochemicals On Cellular and Molecular Events...mentioning
confidence: 99%